THE IMPROVEMENT OF THE PERCEPTION SCALE ON TEACHING TECHNIQUES AND METHODS USED BY INSTRUCTERS OF UNIVERSITY STUDENTS - Ebru BOZPOLAT (Fırat University, 2019)
The purpose of this research is improved a measuring instrument as proven of validated and reliability to determine the perceptions related of teaching methods /technique that is used in education-teaching period by instructers of university students. Population of the study, consists of students that is received education faculty of literature, sciences, economics and administrative sciences, medical faculty, engineering and faculty of education in Cumhuriyet University. The research sample consists of 749 students that is received education relevant departments in Cumhuriyet University. In accordance with purpose of study, was pursued scale improvement methods in the likert type of scale with developed to determine the perceptions related of teaching methods and techniques that is used in education-teaching period. For this, first of all was set an purpose and in accordance with this purpose, concerned the literature was scanned . Then respectively, was put into the final form of scale by making primary implementation and base implementation, preparing the scale of materials and expertising for content validity. In the analysis of data, were used exploratory factor analysis and confirmatory factor analysis. In addition to this was performed the reliability study. As a result exploratory factor analysis was obtained a construction 22 items which consists of 4 components. For screening goodness of fit the structure factor which was made as a result of confirmatory factor analysis, the form chi–square value was reached the conclusion meaning of X2 =367.66, sd=203, p= .00, X2/sd=1.81. Fit index values were acquired as RMSEA= .033, SRMR=.037, CFI= .99, NFI= .98, RFI=.97, IFI= .99 and GFI= .95. Calculated of fit values were found to be within acceptable limits. The internal consistency reliability co-efficient (Cronbach Alfa); the full of the scale .91 , the components of the scale between .72 and .87 was calculated . The two half of reliability co-efficient; the full of the scale .81 , the components of the scale between .70 and .85 was calculated. The two half of the reliability co-efficient of Guttman; the full of the scale .92 , the components of the scale between .70 and .85 was calculated . All the components of the perception scale on teaching methods and techniques were found to have a high reliability.